The Effect of Providing Balanced Nutrition Education on Nutritional Knowledge, Diet, and Body Mass Index (BMI) in Adolescents - Azzah Abidah Azro; Sutomo Rum Teguh Kaswari; Annasari Mustafa (Nutri-Sains: Jurnal Gizi, Pangan dan Aplikasinya, 2025)
Obesity is an overnutrition problem that has not yet received special attention from the government or society. Adolescents are easily influenced by their peers. Providing balanced nutrition education to adolescents at SMA Negeri 1 Singosari using the peer education method is expected to improve nutritional knowledge, enhance dietary patterns, and reduce the overweight adolescents' body mass index (BMI). A screening was conducted among tenth-grade students, identifying 60 students with a BMI ≥25.1 kg/m². The instruments included a nutritional knowledge questionnaire, Semi-Quantitative Food Frequency Questionnaire (SQ-FFQ) to assess dietary patterns, weight and height measurements to determine BMI. The results showed an increase in knowledge scores; however, it was not statistically significant (p-value = 0.106). There was a significant effect on the reduction of adolescents' BMI (p-value = 0.023). Dietary patterns showed improvement in average daily intake, frequency of consumption, and food preparation methods, although the intake of plant-based proteins, vegetables, and fruits remained below the Balanced Nutrition Guidelines. The results of this study imply that balanced nutrition education using the peer tutor method can be an effective approach to reduce BMI and encourage healthier eating patterns in obesity adolescents.